ANALISIS PENDAPATAN PETANI PINANG DI DESA SUNGAI BERAS KECAMATAN MENDAHARA ULU KABUPATEN TANJUNG JABUNG TIMUR - Mariyanis Sahputri; Diliza Afrila (SJEE (Scientific Journals of Economic Education), 2020)
This study aims to find out the factors that led to the decline in betel nut prices in Sungai Beras Village, Mendahara Ulu District, East Tanjung Jabung Regency, the selling price of betel nuts and the welfare of betel nut farmers. Based on the research results, it was found that the factors that caused the decline in the income of the betel nut farmers, however, did not find a definite solution to increase their income. On average, farmers find it difficult to meet their daily needs. Thus it can be concluded that the welfare of betel nut farmers still depends on the selling price of areca nut. Because areca nut is still the main livelihood for farmers in Sungai Beras Village, Mendahara Ulu District, East Tanjung Jabung Regency.